Pengaruh Return On Asset (ROA), Price Book Value (PBV), Debt To Equity (DER) Dan Economyc Value Added (EVA) Terhadap Return Saham Pada Perusahaan Sektor Property & Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Indo Uleng; Trisnadi Wijaya (Publikasi Riset Mahasiswa Manajemen, 2026)
This study aims to analyze the effect of ROA,PBV, DER, and EVA on the stock returns of companiesin the property and real estate sector listed on theIndonesia Stock Exchange from 2019 to 2023. This studyuses a quantitative approach with secondary data andpurposive sampling technique involving 39 companies,totaling 195 observations. Data analysis uses multiplelinear regression. The study shows that PBV has asignificant effect on stock returns, while ROA, DER, andEVA do not have a significant effect. These findingsindicate that investors pay more attention to the marketvalue of the company compared to other fundamentalaspects. Keywords: ROA, PBV, DER, EVA, Stock Return